3‐acetylpyridine‐induced degeneration in the adult ascidian neural complex: Reactive and regenerative changes in glia and blood cells. Issue 8 (11th December 2014) - Medina, Bianca N. S. P.; Santos de Abreu, Isadora; Cavalcante, Leny A.; Silva, Wagner A. B.; da Fonseca, Rodrigo N.; Allodi, Silvana; de Barros, Cintia M.
ABSTRACT Ascidians are interesting neurobiological models because of their evolutionary position as a sister‐group of vertebrates and the high regenerative capacity of their central nervous system (CNS). We investigated the degeneration and regeneration of the cerebral ganglion complex of the ascidian Styela plicata following injection of the niacinamide antagonist 3‐acetylpyridine (3AP), described as targeting the CNS of several vertebrates. For the analysis and establishment of a new model in ascidians, the ganglion complex was dissected and prepared for transmission electron microscopy (TEM), routine light microscopy (LM), immunohistochemistry and Western blotting, 1 or 10 days after injection of 3AP. The siphon stimulation test (SST) was used to quantify the functional response. One day after the injection of 3AP, CNS degeneration and recruitment of a non‐neural cell type to the site of injury was observed by both TEM and LM. Furthermore, weaker immunohistochemical reactions for astrocytic glial fibrillary acidic protein (GFAP) and neuronal βIII‐tubulin were observed. In contrast, the expression of caspase‐3, a protein involved in the apoptotic pathway, and the glycoprotein CD34, a marker for hematopoietic stem cells, increased. Ten days after the injection of 3AP, the expression of markers tended toward the original condition. The SST revealed attenuation and subsequent recovery of the reflexes from 1 to 10 days after 3AP. Therefore, we have developed a new method to study ascidian neural degeneration and regeneration, and identified the decreased expression of GFAP and recruitment of blood stem cells to the damaged ganglion as reasons for the success of neuroregeneration in ascidians. © 2014 Wiley Periodicals, Inc. Develop Neurobiol 75: 877–893, 2015